Implementasi Metode AHP TOPSIS pada Pemilihan Santri Berprestasi - Amanatulloh, Sahrul Adi; Soelistijadi, R. (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2022)
Islamic boarding schools are one of the traditional educational institutions that study Islamic values daily, the selection of student scholarships still uses manual so that it will affect the results of scholarship selection and data input still uses handwriting so that storing files for a long time is likely to be damaged due to exposure to water. or torn, it is necessary to create a system that helps the scholarship selection process using the AHP (Analytical Hierarchy Process) and TOPSIS (Technique for Order Preference by Similarity to Ideal Solution) methods. In AHP there are 4 (four) stages, including: determining the criteria, determining the pairwise comparison table, calculating the criterion value matrix and the consistency ratio. The criteria used refer to the requirements for the selection of students at the al-Madani Islamic boarding school. AHP is used to calculate the weight of each criterion and TOPSIS for ranking, the first step is to calculate the AHP method by inputting criteria and determining pairwise comparison tables to produce weights between criteria. The TOPSIS implementation includes: alternative data, alternative assessments, weighted normalization, determining positive and negative ideal solutions, and calculating the distance of positive and negative ideal solutions so as to produce a ranking, a decision support system for selecting outstanding santri scholarships with the highest preference value, namely: 0.69123910870266 so that the results This can be a benchmark for scholarship recipients based on predetermined criteria.